Impact of Curriculum Management on the Quality of Graduates at MI Yusuf Abdussatar Kediri, West Lombok Regency - Abdul Sahid (Edumaspul: Jurnal Pendidikan, 2023)
Curriculum management is a comprehensive, systemic and systematic cooperative system for realizing curriculum achievement. This research was designed as a qualitative approach and took the research location in Madrasah Ibtidaiyah Yusuf Abdussatar Kediri, West Lombok Regency. Observation, interviews, and documentation carry out data collection procedures. Data analysis techniques use data reduction, data presentation, and conclusions. Meanwhile, data validity is checked by extending participation, observation diligence, triangulation of peer reviewing data and using sufficient references. Research findings show that 1) how curriculum management on the quality of graduates is: a) forming a curriculum development team, b) making the basic framework of the curriculum, c) analyzing the context in the curriculum, d) analyzing the characteristics in the curriculum made, e) organizing the curriculum so that the curriculum has a regular structure in the curriculum itself, f) preparing an appropriate learning implementation plan to achieve the expected goals, and g) curriculum evaluation; 2). How are the curriculum management steps towards the quality of graduates, namely: a) implementation of the right curriculum so that the quality of graduates is achieved, b) carrying out extracurricular activities in the curriculum, and c) carrying out appropriate intra-curricular activities by the curriculum made.